2012
DOI: 10.1111/j.1530-0277.2012.01797.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Development of Impulsivity and Sensation Seeking from Childhood into Adolescence and Their Relation to Alcohol Use

Abstract: Background Pronounced differences in drinking behavior exist between African Americans and European Americans. Disinhibited personality characteristics are widely studied risk factors for alcohol use outcomes. Longitudinal studies of children have not examined racial differences in these characteristics, in their rates of change, or whether these changes differentially relate to adolescent alcohol use. Methods Latent growth curve modeling was performed on seven annual waves of data on 447 African American an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 42 publications
6
55
1
2
Order By: Relevance
“…The only mental health indicator that had unequal mean scores was sensation seeking; students identifying as White reported the greatest levels of sensation seeking. These findings are also in alignment with previous research (e.g., Arnett, 1996;Jaffe & Archer, 1987;Pedersen, Molina, Belendiuk, & Donovan, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…The only mental health indicator that had unequal mean scores was sensation seeking; students identifying as White reported the greatest levels of sensation seeking. These findings are also in alignment with previous research (e.g., Arnett, 1996;Jaffe & Archer, 1987;Pedersen, Molina, Belendiuk, & Donovan, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Adolescence is strongly associated with a heightened instability in these traits, potentially influenced by neurodevelopmental changes in this developmental stage (Crone & Dahl, 2012; Ernst & Fudge, 2009; Steinberg, 2008; Steinberg et al, 2008). Sensation seeking increases in early adolescence, with a peak in middle adolescence, and decreases closer to young adulthood (Littlefield et al, 2016; Romer & Hennessy, 2007; Steinberg et al, 2008); however, some studies have found an increase in sensation seeking moving toward young adulthood (Collado et al, 2014; Harden & Tucker-Drob, 2011; Pedersen et al, 2012). Negative urgency and positive urgency increase during early adolescence (i.e., 11–13 years) and decline across later adolescence (Littlefield et al, 2016).…”
Section: Impulsive Behavior Across the Lifespan: Implications For mentioning
confidence: 99%
“…Sensation seeking has been studied in terms of its relationship to substance use [4-16], sexual risk taking [17-21], and psychopathology [5, 22-27] among adolescents. It is believed to peak at around age 16 [12, 28], is usually greater in males than females [29-32] and in whites compared to African Americans [6, 24, 33].…”
mentioning
confidence: 99%